The use of injectable chondroitin sulfate in combination with dosed physical exercise for the treatment of patients with hand osteoarthritis - L. V. Vasilyeva; E. F. Evstratova; E. Yu. Suslova (Современная ревматология, 2020)
Objective: to evaluate the efficiency and the safety of treatment with injectable chondroitin sulfate (ICS) in combination with dosed physical exercise (exercise therapy (ET)) for hand osteoarthritis (HOA).Patients and methods. A study group consisted of 68 patients with HOA; the diagnosis of which was established in accordance with the 1991 American College of Rheumatology (ACR) criteria. The investigators identified two groups: 1) 36 women and 4 men; mean age, 62.2±3.4 years (a study group); 2) 20 women and 8 men; mean age, 61.7±6.5 years (a control group). Group 1 patients received treatment with 25 intramuscular ICS (Chondroguard) injections per cycle and underwent ET under the guidance of a trainer. In the first 3–5 days, the patients could take nonsteroidal anti-inflammatory drugs (NSAIDs). Group 2 patients were prescribed a magnetic therapy cycle (alternating pulsed magnetic field, 15–20-minute hand exposure, a total of 10 sessions). They could also take NSAIDs within the first 3–5 days. A visual analogue scale (VAS, mm) was used to analyze hand pain severity over time: at baseline, at 3 weeks, and at 3 months after the start of treatment.Results and discussion. The dynamics of VAS joint pain was statistically more significant in Group 1 than in Group 2: 69.1±2.83 and 71.1±2.15 mm at baseline; 42.6±1.16 and 57.14±1.96 mm at 3 weeks (p<0.05), and 36.4±2.96 and 62.8±3.26 mm at 3 months (p<0.001). Similarly, Group 1 versus Group 2 showed a greater improvement in indicators, such as a decrease in the duration of morning stiffness in the hands and an increase in their grip strength. No adverse reactions requiring discontinuation of treatment or special therapy were noted in both groups.Conclusion. The investigation showed the advantage of ICS used in combination with ET over magnetotherapy in the treatment of patients with HOA.